Decoding Online Shopping Behavior in Malaysia: The Critical Influence of Consumer Trust - Krishnan, Vijayaletchumy; Jayabalan, Neeta; Guo, Jiayuan; Susanto, Perengki (Journal of Ecohumanism, 2024)
The rapid evolution of e-commerce has heightened the importance of consumer trust, especially regarding privacy and security. This study investigates how key trust factors; security, privacy, transparency, and reliability affect consumer trust and online shopping behavior. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), the research examines how these factors impact consumer confidence in online transactions and their purchasing decisions. Findings indicate that privacy concerns negatively affect consumer trust, while security measures and transparency positively influence trust. The study offers valuable insights for e-commerce platforms to enhance trust-building strategies and improve consumer behavior and engagement. By addressing these trust dynamics, the research provides practical implications for strengthening e-commerce reliability and boosting online shopping behavior in Malaysia.